(untitled) (Journal of Science and Technology, 2016)
Organization and implementation of day-care pediatric surgery in Komfo Anokye Teaching Hospital (KATH) has been well established for the past six years. Reasons for this development include: maximum convenience for the parents relatives, decongestion of the in-patient wards; lessened emotional trauma for the child due to separation from the parents as an to patient; reduction of the financial loss to the hospital as a result of parents not being able to pay their children fees and therefore, being declared paupers or absconding after having received several days inpatient treatment; improvement in the anesthetic services; elimination of hospital infection; and finally, increase in the number of children needing surgical treatment as inpatients in small and congested wards. The financial benefit to the parents sometimes in-volved a reduction in the costs to about 70% of inpatient treatment. Financially too, the hospital was better off since all patients paid the necessary fees before surgery; besides more and more children benefited from this mode of service.